An analysis of first years senior high school students' mental models: a case study on the concept of straight motion - Amiruddin, Mohd Zaidi; Samsudin, Achmad; Suhandi, Andi; Costu, Bayram (Journal of Education and Learning (EduLearn), 2025)
Difficulties in understanding physics concepts are often experienced by students such as in the material of regular straight motion. This study aims to describe the mental models of first-year secondary school students on regular straight-line motion. This research utilized a case study method of 167 students at the secondary level with an average age of 16-17 years. The mental model test has been utilized form of essay questions The mental model test has been utilized form of essay questions with two sub-materials on the regular straight motion. The data were analyzed referring to the descriptive mental model assessment rubric in the related literature. The rubric maps the level of student understanding which is then categorized into scientific, synthetic, and initial mental model categories. The results stated that students' mental models were dominated in the initial category with respective percentages for both sub-categories of 60% and 90%. In addition, there are still terms of understanding that cannot be distinguished by students so it becomes one of the causes of their unscientific mental models. Based on these results, it is suggested that for further research, alternative teaching materials are needed that can have an impact on improving students' mental models.